Sustainable Land Use Planning Solutions for Water Supply Reservoirs in Serbia - Živanović Miljković, Jelena; Pantić, Marijana; Bezbradica, Ljubiša (European Journal of Sustainable Development, 2019)
This paper starts from the fact that spatial and urban planning promote rational land use planning and express interests in the sustainable development of land, water and related resources and infrastructure. The authors here look for sustainable land use planning solutions in the domain of water management within the spatial plans. A starting point of this paper is the fact that integration of water management issues (i.e. drinking water management) into land use planning is essential in achieving sustainable development. Considering this, the paper focuses on analysis of land use planning solutions given within three spatial plans that include areas of water supply reservoirs. The authors give an analysis of the set of measures prescribed by zoning ordinances within spatial plans concerning water protection and protection from water (i.e. flood water evacuation). The authors conclude that analyzed spatial planning documents give sustainable land use solutions, since land use planning, through the zoning, represent a starting point in water protection. Keywords: Spatial Planning, Sustainable Land Use, Water Management, Water Reservoirs, Serbia